Investigation of in vitro anti-trichomoniasis effect of Helianthemum ledifolium L. (Mill.) varieties against Trichomonas vaginalis (Annals of Medical Research, 2023)
Aim: Trichomonas vaginalis is a flagellated protozoan that is sexually transmitted and causes trichomonosis. It is one of the public health problems caused by sexually transmitted diseases. However, for a long time it received less attention than other parasitic and sexually transmitted diseases. Recently, the parasite has been associated with increased cases of HIV, miscarriages, infertility, pelvic inflammatory diseases and cervical and prostate cancers. Given the increasing resistance to the nitroimidazole class of drugs used in its treatment, different alternatives are needed. New drugs are increasingly being derived from natural products containing a large number of active compounds. In addition, different synthetic products or derivatives from old drugs are also used as an alternative for the treatment of trichomonosis. In this study, it was investigated whether Helianthemum ledifolium variates [H. ledifolium (L.) Miller var. ledifolium (L.) Miller;H. ledifolium (L.) Miller var. microcarpum Willk.; H. ledifolium (L.) Miller var. lasiacarpum (Willk.) Bornm.] growing naturally in Turkey. Herein, aqueous and methanolextracts prepared by maceration method from the above-ground parts were evaluated for their in vitro anti-trichomoniasis activity against Trichomonas vaginalis. Materials and Methods: The extracts prepared from H. ledifolium taxa were added to the parasite grown in culture and checked at regular intervals to check for viability. Each measurement was performed twice and averaged. Descriptive statistics of the data set are expressed as mean ± standard deviation (SD). The values of lethal doses were determined using probit analysis for certain periods of time depending on specific concentrations (LD50 and LD90).Results: Extracts prepared from H. ledifolium variates inhibited the growth of T. vaginalis in a dose-dependent manner starting from the 4th hour. LD50 values for 4th hour were 2.39 mg for ledifolium water extract, 6.63 mg for ledifolium methanol, 2.39 mg for lasiocarpium water, 1.99 mg for lasiocarpium methanol, 5.77 mg for microcarpium water, 8.76 mg for microcarpium methanol.Conclusion: This study data showed us that Helianthemum ledifolium varieties may be a potential natural medicine that can be used in parasite treatment. However, standardization studies should be carried out on plant extracts, and in vitro studies should be supported by in vivo studies.
Keywords: Anti-protozoan; Anti-Trichomonas vaginalis activity; Helianthemum ledifolium varieties; Trichomonosis